Framing prostitution policies. A comparision of Slovenia and Austria - Hrzenjak, Majda; Jalusic, Vlasta; Sauer, Birgit; Tertinegg, Karin (The Greek Review of Social Research, 2016)
In the article, the authors explore how prostitution policies as explicitly gendered policies are framed in two countries, Austria and Slovenia. These countries share many elements of historical, cultural and religious setting even if their political systems and cultures developed in different ways. The background of prostitution policies, policy environment and actors in both countries is outlined. The authors then present the frames found in the two countries and compare them. In the last part of the paper, first comparative explanations for differences and similarities in framing and policy outcome are given. The main argument is that frames on prostitution have undergone considerable changes in both countries, but conceptualisations of women as the «Other» and of «voluntary versus forced» prostitution are central to the debates in both countries.